Information Technology Revolution: Its Impact on the World of Work in the Digital Era - Muhammad Riza Syahputra; Suherman Candra (IHSA Institute, 2025)
This study aims to identify and analyze how the process of the information technology revolution increases company productivity, as well as how the government acts to reduce unemployment caused by the replacement of human tasks by information technology in several industrial companies in Indonesia. The research method uses a qualitative descriptive approach with purposive sampling for data collection, and data is gathered through documentation study. Based on the research findings, it can be concluded that several ways businesses become more productive due to the IT revolution, including process automation, efficient collaboration and communication, data and big data management, improved operational efficiency, and customer service digitization. It can also be concluded that the preventive measures taken by the government to reduce the impact of information technology on increasing unemployment include enhancing education and training in information technology skills, developing the digital economy and creating job opportunities, providing technological infrastructure to train potential human resources in regions, as well as setting regulations and policies to adjust the labor market.